Land Value Potential Zonation : Implication Towards Urban Planning - Revi Mainaki; Anita Eka Putri; Dwiyono Hari Utomo (Department of Geography Education, University of Jember, 2020)
Potential land prices are strongly influenced by various factors, Cimahi City has three sub-districts displaying unique characteristics, since it is located between two districts and one large city, which affects the potential price of land. The potential price of land is crucial to identify, especially in determining the policies of related agencies, the purpose of this research was to zoning potential land prices in Cimahi City. This study engaged a quantitative approach utilizing data collection technique in the form of observation, literature, documentation, and interviews, then analysis was conducted using a GIS which composed of assessment, weighting, coating, and buffering. The study population was all sub-districts in Cimahi. The research samples were taken from several sub-districts which were influenced by districts and cities characteristics indicators such as accessibility, land usage, and land ownership status. The results showed land prices potential was classified as low, medium, and high which was derived by several indicators. It could be concluded that the potential land price is strongly influenced by the surrounding area features, especially urban and district infrastructure. Keywords: Land Value Potential; Zonation; Urban Planing Copyright (c) 2020 Geosfera Indonesia Journal and Department of Geography Education, University of Jember This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License